Association of croup with asthma in children: A cohort study. Issue 35 (September 2017) - Lin, Sheng-Chieh; Lin, Hui-Wen; Chiang, Bor-Luen
Abstract : Abstract: Asthma and croup are common inflammatory airway diseases involving the bronchus in children. However, no study has reported the effects of urbanization, sex, age, and bronchiolitis on the association of croup and its duration with asthma development. We used the Taiwan Longitudinal Health Insurance Database (LHID) to perform this population-based cohort study; here, the cluster effect caused by hospitalization was considered to evaluate the association between croup and asthma development and the risk factors for asthma in children of different age groups. We evaluated children with croup aged <12 years (n = 1204) and age-matched control patients (n = 140, 887) by using Cox proportional hazards regression analysis within a hospitalization cluster. Of all 142, 091 patients, 5799 (including 155 with croup [419 per 1000 person-y] and 5644 controls [106 per 1000 person-y]) had asthma during the 5-year follow-up period. During the 5-year follow-up period, the hazard ratios (HRs [95% CIs]) for asthma were 2.10 (1.81–2.44) in all children with croup, 2.13 (1.85–2.46) in those aged 0 to 5 years, and 2.22 (1.87–2.65) in those aged 6 to 12 years. Children with croup aged 7 to 9 years had a higher HR for asthma than did those in other age groups. Boys with croup had a higher HR for asthma. The adjusted HR for asthma was 1.78 times higher in children with croup living in urban areas than in those living in rural areas. In conclusion, our analyses indicated that sex, age, bronchiolitis, and urbanization level are significantly associated with croup and asthma development. According to our cumulative hazard rate curves, younger children with croup should be closely monitored for asthma development for at least 3 years.